Azacitidine Treatment in Patients with Myelodysplastic Syndrome, Chronic Myelomonocytic Leukemia Type 2 and Acute Myeloid Leukemia According to their Cytogenetic Findings - Nikolova D.; Yordanov A.; Radinov A. (Acta Medica Bulgarica, 2021)
Introduction: Azacitidine is one of the hypomethylating agents available for the treatment of elderly patients with myelodysplastic syndrome (MDS) or acute myeloid leukemia (AML). It is also used as an appropriate treatment of chronic myelomonocytic leukemia (CMML) in the real life setting. As treatment of AML and CMML is not curative, and allogeneic stem cell transplantation (allo-SCT) remains traditionally the only option, significant clinical benefits by hypomethylating agents have been reported. According to the available data, 16% of subjects with MDS who received azacitidine had a complete or partial normalization of blood cell counts and bone marrow morphology, while two-thirds of patients who required blood transfusions no longer needed them. Nevertheless, it can also be hepatotoxic in patients with severe liver impairment and extensive liver tumors.